Burning rice for fuel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Engineers at the Indian Institute of Technology in NewDelhi have come up with plans to use hard cakes of rice husk costing the equivalent of 12 (US) cents each as cooking fuel. An experiment in Nepal has shown that two of these cakes can provide...